EVALUATION OF TRAVEL TIME RELIABILITY IN URBAN AREAS USING MOBILE NAVIGATION APPLICATIONS IN JORDAN - Alomari, Ahmad; Al-Omari, Aslam; Aljizawi, Wafa (Journal of Applied Engineering Science, 2022)
This study aims to assess the Travel Time Reliability (TTR) in urban areas in Irbid city, Jordan, using a mobile application (Ultra GPS Logger), which retains the current location, speed, and time every three seconds. The study evaluated the TTR at the Origin-Destination (OD) level and the segment level. Each OD was divided into several segments with different interruption types to determine which segments have the lowest reliability and the most extended delay. The evaluation was based on several measures according to the Federal Highway Administration (FHWA), such as the buffer time, Buffer Index (BI), Travel Time Index (TTI), 95th percentile, standard deviation, and Coefficient of Variation. Chi-Square test for independence was carried to study the association between the period during the day, day of the week, and section type with the BI Level, and other combinations. Results showed that the normal sections, without traffic signals and roundabouts, had a significant effect on TTR compared with 3-Leg intersections, 4-Leg intersections, and roundabouts. Results also confirmed that trips reliability does not mean there is no delay or congestion, but there is some certainty in travel time prediction for a specific route and journey.
Keywords: travel time reliability, prediction, navigation, origin-destination